Structured periodic rehabilitation intervention sessions to stroke patients. A longitudinal review. - Aziz, NA; Nashrah, H; Fadilah, AZ; Ali, MF; Zawawi, S; Katijah, A (Penerbit UKM, 2011)
Despite evidence showing that structured rehabilitation after stroke improves functional outcomes, providing seamless rehabilitation from hospital to community has been elusive. The service provided should be able to accommodate variable degree of impairments and needs of the stroke survivors. This study aimed to assess the outcome of a multidisciplinary-based outpatient rehabilitation service for stroke patients living in the community. Patients who were discharged from Universiti Kebangsaan Malaysia Medical Centre after an acute stroke were referred to the Combined Stroke Rehabilitation Clinic (CSRC). Post stroke patients were assigned individually designed programs which were problem based and used task specific activities to achieve desired goals. Patients were reviewed on a regular basis either up to completion of the 2 year-program, or are able to be discharged to the community, whichever is earlier. Modified Barthel Index (MBI) and Berg Balance Scores (BBS) were used for monitoring. A total of 68 patients were managed in CSRC for two years since its initiation, with mean age of 62.4 years (SD 12.4) with the mean duration of stroke when first reviewed in CSRC was 11.5 months (SD 11.9). Majority of patients (64.7%) received either two or three types of intervention. Both MBI and BBS demonstrated significant improvement over 12-months period (p value of 0.006 and 0.017 respectively). CSRC proved that structured rehabilitation intervention was beneficial in terms of functional status and improvement in balance to post-stroke patients.